2011
DOI: 10.4491/ksee.2011.33.11.804
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Theoretical Adsorption Models for Studies on Adsorption Properties of Adsorbents(II)

Abstract: The aim of this study is to evaluate the applicability of adsorption models for understanding the thermodynamic properties of adsorption process. For this study, the adsorption isotherm data of NO3-N ion onto a commercial anion exchange resin obtained at various experimental conditions, i.e. different initial concentrations of adsorbate, different dosages of adsorbent, and different temperatures, were used in calculating the thermodynamic parameters and the adsorption energy of adsorption process. The Gibbs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
(1 reference statement)
1
3
0
3
Order By: Relevance
“…Like the intraparticle diffusion model, when the plot using Equation ( 13) is linear and passes through zero regardless of K s , A, or V, it suggests that film diffusion governs the adsorption kinetic process [56]. To carefully predict the external diffusion, Figure 8a was segregated with two regions in Figure 8b, and then showed that the slope sharply increased at the beginning (≤ 1 h) and gradually decreased after 1 h, which is a similar trend as that found in a prior study [47]. Note that the simplified Equation ( 13) is comparable with the LPFO model in Equation ( 9); additionally, Figure 8 is very similar to Figure 5 in the current study.…”
Section: External Mass Transfersupporting
confidence: 80%
See 2 more Smart Citations
“…Like the intraparticle diffusion model, when the plot using Equation ( 13) is linear and passes through zero regardless of K s , A, or V, it suggests that film diffusion governs the adsorption kinetic process [56]. To carefully predict the external diffusion, Figure 8a was segregated with two regions in Figure 8b, and then showed that the slope sharply increased at the beginning (≤ 1 h) and gradually decreased after 1 h, which is a similar trend as that found in a prior study [47]. Note that the simplified Equation ( 13) is comparable with the LPFO model in Equation ( 9); additionally, Figure 8 is very similar to Figure 5 in the current study.…”
Section: External Mass Transfersupporting
confidence: 80%
“…Attempts have been made to overcome the poor relation for the LPFO model. Na and Park (2011) [47] and Simonin (2016) [40] separated the times in terms of the initial from the other times. Both results show that the calculated parameters at the initial time can be relatively compared to the nonlinear equation and PSO; however, the rest of the region should be ignored, indicating that a different adsorption mechanism is expected [47].…”
Section: Linear Pfo and Psomentioning
confidence: 99%
See 1 more Smart Citation
“…Where qe (mg g -1 ) is the quantity of adsorbate at equilibrium, qt is the adsorbed amount at a given interval (t), while K2 is constant rate calculated from straight-line plot of the above equation [118].…”
Section: Pseudo-second-ordermentioning
confidence: 99%
“…하로 아연에 대한 흡착제로 충분히 활용 가능할 것으로 판단된다. 또한 흡착강도 (1/n)값이 >1, 1, <1 일 때 각각 S형, C형 및 L형 등온 흡착특성을 갖게 된다고 보고하였는데(Na et al, 2011), 본 연구에서 SCGB에 의한 아연의 흡착은 L형 등온선과 일치하였다. L형 등온선은 흡착질이 흡착제의 표면에 단층 (monolayer)으로 흡착하는 경우에 나타나 는 것으로 알려져 있다(Na et al, 2011).또한 SCGB의 아연흡착특성은 반응시간별로 조사되었으며, 그 결과는Fig.…”
unclassified